Patient-specific quality control for intensity-modulated radiation therapy and volumetric-modulated arc therapy using electronic portal imaging device and two-dimensional ion chamber array. Issue 1 (5th September 2018) - Kausar, Abu; Mani, Karthick R.; Azhari, Hasin A.; Zakaria, Golam A.
Abstract: Aim: The purpose of this study was to develop the patient-specific quality control (QC) process by most commonly used dosimeters in Bangladesh and recommend a suitable passing rate for QC, irrespective of the dosimetric tools used. Materials and methods: Intensity-modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT) plans of five head-and-neck (HN) and five prostate patients were selected for the patient-specific QC. These plans were generated using the Eclipse TPS v11·0 (Varian Medical Systems, Inc., Palo Alto, CA, USA) 6 MV X-ray from a Varian TrueBeam linear accelerator (Varian Medical Systems, Inc.) for each case. Each IMRT and VMAT plans were measured by two-dimensional (2D) ion chamber arrays (I'matriXX) and electronic portal imaging devices (EPID), respectively. The passing rates of the dosimetric tools were calculated using criteria of 3%/3 mm. Results: The average passing rates (±SD) of I'matriXX for prostate and HN were 97·9±0·76 and 98·88±0·24, respectively. For VMAT verification, the average passing rates of EPID for prostate for arc1 and arc2 were 96·15±0·49 and 97·8±0·70, respectively; similarly, for HN the rates were 97·85±0·63 and 97·2±0·56, respectively. Conclusion: The results showed that both the dosimeters can be used in patient-specific QC, although the EPID-based IMRT and VMAT QC is more advantageous in terms of time-saving and ease of use. Hence, for patient-specific QC, one can use the ion chamber arrays (I'matriXX) or EPID in hospital, but the systems need to be cross-checked.